The Tumor Microenvironment as a Regulator of Endocrine Resistance in Breast Cancer - Diaz Bessone, María Inés; Gattas, María José; Laporte, Tomás; Tanaka, Max; Simian, Marina (Frontiers in Endocrinology, 2019)
Estrogen receptor positive breast tumors represent over 70% of diagnosed breast cancers. Depending on the stage at which the tumor is detected, HER2 status and genomic risk, endocrine therapy is combined with either radio, chemo and/or targeted therapy. A growing body of evidence supports the notion that components of the tumor microenvironment play specific roles in response to treatment and that strategies targeting these key interactions with tumor cells could pave the way to a new generation of therapies. In this review, we analyze the evidence supporting the role played by the different components of the tumor microenvironment in hormone receptor positive breast cancer. In particular we focus on the immune system, carcinoma associated fibroblasts and the extracellular matrix. Further insight into the cross talk between these constituents of the microenvironment and the tumor cells may lead to therapies that eliminate disseminated metastatic cells early on, and thus reduce distant disease relapse which is the main cause of death for patients who are diagnosed with this disease.